2010
DOI: 10.1109/tpwrd.2010.2051960
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Home Appliances for Power Distribution System Harmonic Analysis

Abstract: Single-phase diode-bridge converter-based loads have become a common load type in power distribution systems. It has become very important to consider their harmonic impact on the power quality (PQ) of power distribution systems because they now represent a large percentage of residential loads. One of the challenges in modeling these loads for harmonic analysis is the lack of model parameters. This paper proposes an approach to estimate the model parameters, suitable for use in frequency-domain harmonic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…Finally, there are hybrid approaches which combines various types of modeling. For instance, Yong et al (2010) combine measurements and analytic examination to obtain the model for full-wave rectifier-based loads.…”
Section: Electrical Modelmentioning
confidence: 99%
“…Finally, there are hybrid approaches which combines various types of modeling. For instance, Yong et al (2010) combine measurements and analytic examination to obtain the model for full-wave rectifier-based loads.…”
Section: Electrical Modelmentioning
confidence: 99%
“…It is reported that 10% smaller harmonic current magnitudes can be seen when phase angle information is included compared to the simple summing of magnitudes without phase angle values [10]. The attenuation effect is dependent only on the phase angle, but the effect's severity is dependent on the magnitude of the harmonic voltage [11].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Because the DC filter capacitance has six charging-discharging processes in every cycle, the method described in the literature [21] can be used to calculate the DC capacitance as follows:…”
Section: Estimation Of the DC Load Resistance R And Filter Capacitance Cmentioning
confidence: 99%
“…It is difficult to obtain detailed equivalent circuit parameters for each charger. Previous studies [21] have proposed a method using the measured AC current waveform of a single-phase uncontrolled rectifier under given voltage conditions to estimate the parameters of the harmonic analysis circuit. However, for the commonly used three-phase uncontrolled rectification charger, the charging current has two modes: the continuous conduction mode (CCM) and discontinuous conduction mode (DCM), which is different from that of the single-phase rectification circuit.…”
Section: Introductionmentioning
confidence: 99%